Molecular characterization of an inhibitor of apoptosis protein (IAPs) in freshwater pearl mussel, Hyriopsis schlegelii - Di Wu (Bioengineered, 2019)
The inhibitor of apoptosis proteins (IAPs) played important roles in inhibiting the apoptosis of tumor cells by regulating caspase activity in mammals. In this study, we first cloned the full-length cDNA sequence of IAPs gene (designated as Hs-IAPs) in Hyriopsis schlegelii. The Hs-IAPs gene contained an open reading frame of 1719 nucleotides, encoding a predicted protein of 572 amino acids. qRT-PCR assay indicated that the Hs-IAPs gene was ubiquitously expressed in different tissues, and the highest expression level was in gills. Furthermore, we purified and obtained the recombinant protein of Hs-IAPs which showed a molecular weight of 82.5 kDa. We used H2O2 stimulation experiment to explore the possible function of Hs-IAPs. The results showed that the percentage of viable cells significantly increased following the Hs-IAPs concentration. These indicated that the Hs-IAPs may play a role in anti-oxidation causing by H2O2, and its anti-oxidative may be crucial in the process of apoptosis.